Adaptive fault tolerant control for time-varying delay system with actuator fault and mismatched disturbance. (June 2019) - Guo, Bin; Chen, Yong
Abstract: In this paper, the fault tolerant control (FTC) problem for a class of continuous Lipschitz nonlinear systems with actuator fault, mismatched disturbance, and time-varying delay is investigated. An adaptive integral sliding mode fault tolerant control (AISMFTC) technique is proposed. First, a composite observer is designed to estimate the states and disturbance simultaneously, by introducing a sliding mode observer, the actuator fault is reconstructed. Then, in accordance with the estimated information, an AISMFTC method is designed. In the AISMFTC scheme, two adaptive laws and compensators are contained to compensate the observer errors, deal with the effects of actuator fault and attenuate the disturbance. Furthermore, the H ∞ performance is considered for the robustness of the system. Finally, the effectiveness of the proposed method is illustrated by two examples. Highlights: A composite sliding mode observer is proposed to estimate the unknown state, mismatched disturbance and actuator fault. The mismatched disturbance is divided two parts which are compensated by the disturbance compensator and attenuated within H-infinite level, respectively. An adaptive integral sliding mode fault tolerant control scheme is constructed, in which two adaptive laws and compensators are contained to stabilize the system.